2019
DOI: 10.1093/annonc/mdz052
|View full text |Cite
|
Sign up to set email alerts
|

Context matters—consensus molecular subtypes of colorectal cancer as biomarkers for clinical trials

Abstract: The Colorectal Cancer Subtyping Consortium identified four gene expression consensus molecular subtypes, CMS1 (immune), CMS2 (canonical), CMS3 (metabolic), and CMS4 (mesenchymal), using multiple microarray or RNA-sequencing datasets of primary tumor samples mainly from early stage colon cancer patients. Consequently, rectal tumors and stage IV tumors (possibly reflective of more aggressive disease) were underrepresented, and no chemo- and/or radiotherapy pretreated samples or metastatic lesions were included. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
74
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(78 citation statements)
references
References 32 publications
4
74
0
Order By: Relevance
“…[503][504][505] Data showed that the immune desert CMS2 and CMS3 subtypes responded preferably to anti-EGFR or anti-VEGF therapy, and patients in all four CMS classifications might have different mechanisms of immune evasion, which will enable tailored targeted therapy. 504,506,507 There has been a changing trend from a clonal perspective to a clonal-stromal-immune perspective when CRC colorectal cancer, mCRC metastatic colorectal cancer, DR5 human death receptor 5, TGF transforming growth factor, IGF-1R insulin-like growth factor 1 receptor, HGF hepatocyte growth factor…”
Section: Future Directions and Conclusionmentioning
confidence: 99%
“…[503][504][505] Data showed that the immune desert CMS2 and CMS3 subtypes responded preferably to anti-EGFR or anti-VEGF therapy, and patients in all four CMS classifications might have different mechanisms of immune evasion, which will enable tailored targeted therapy. 504,506,507 There has been a changing trend from a clonal perspective to a clonal-stromal-immune perspective when CRC colorectal cancer, mCRC metastatic colorectal cancer, DR5 human death receptor 5, TGF transforming growth factor, IGF-1R insulin-like growth factor 1 receptor, HGF hepatocyte growth factor…”
Section: Future Directions and Conclusionmentioning
confidence: 99%
“…CMS has emerged as a prognostic or predictive marker of targeted therapy; however, substantial work is required for more robust classification of subtypes across different platforms and diverse clinical settings. 116 Ongoing efforts to share and integrate clinical and genomic data could help in the discovery and validation of new actionable targets. 117 Combinations of target blockades and ICIs could provide potential therapeutic opportunities for mCRC cases lacking druggable targets.…”
Section: Strategies Targeting Braf-mutant Crcmentioning
confidence: 99%
“…Taken together, these findings demonstrate the potential for immunotherapies and specifically immune checkpoint inhibitors in the treatment of GI cancer. However, advancing the use of immunotherapies in GI cancer will require combination with chemotherapy, as well as identification of susceptible tumors using specific biomarkers (e.g., PD-1 positive/negative, MSI-H/L, and high/ low tumor mutational burdens) and from among the defined tumor subtypes that describe the origin and TME context of disease [41,42].…”
Section: Infiltrating and Auxiliary Immune Cellsmentioning
confidence: 99%